Efek: Brand Image, Brand Awareness, dan Experiental Marketing Terhadap Loyalitas Nasabah: Bank Muamalat Kota Malang - Sofi Adawiyah; Irmayanti Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of brand image, brand awareness, and experiential marketing on customer loyalty (Bank Muamalat, Malang City). The type of research used is quantitative research. The data collection method uses a questionnaire. The sampling technique used was non-probability sampling with a sample size of 130 people. The analysis technique used is multiple linear regression. Based on the research results, it can be concluded that brand image partially has no effect on customer loyalty of Bank Muamalat, Malang City, brand awareness has an effect on customer loyalty of Bank Muamalat, Malang City, experiential marketing has an effect on customer loyalty of Bank Muamalat, Malang City, and simultaneously, brand image, brand awareness and experiential marketing influence customer loyalty at Bank Mumalata, Malang City.